Current treatment strategies in pediatric gastrointestinal stromal cell tumor - Willobee, Brent A.; Quiroz, Hallie J.; Sussman, Matthew S.; Thorson, Chad M.; Sola, Juan E.; Perez, Eduardo A. (Translational Gastroenterology and Hepatology; Vol 3 (August 2018): Translational Gastroenterology and Hepatology, 2018)
Gastrointestinal stromal tumors (GIST) are exceedingly rare tumors in the pediatric population. As a result, many clinicians either may never see this diagnosis or will encounter it only a few times throughout their careers. Additionally, the more we discover about this disease, it becomes evident that it represents a distinct clinical entity from adult GIST. Many of the treatments and strategies used to combat the adult tumor are either ineffective or may be harmful to the pediatric population with this disease. The unique tumor biology found in pediatric GIST necessitates unique approaches and treatment strategies in order to achieve the best clinical outcome. This review aims to discuss the most recent data available on the different therapeutic modalities utilized in cases of Pediatric GIST.